The Chemical Characteristic and Microbial Diversity of the Hot Spring at Phusang National Park: DOI: 10.32526/ennrj.18.1.2020.04 - Bumrungthai, Sureewan; Duangjit, Sureewan; Somsuwan, Buntom; Inpeng, Somchai (Environment and Natural Resources Journal, 2019)
The Phusang waterfall is located in Phusang National Park in Phayao province, Thailand. The robustness of Phusang’s warm waterfall is regionally recognized as the only one with a temperature range of 35-36 °C which makes it an outstanding place to visit in Thailand. Surprisingly, Phusang waterfall originates from the Phusang warm pool (hot spring). However, data about the bacterial community and characteristics of this water are still obscure. Therefore, this study investigated the bacterial community and characteristics of water in the Phusang hot spring. Tests to determine its physical characteristics such as pH, color and turbidity were performed. Trace elements such as sodium, bicarbonates, iron, and fluoride were detected as chemical characteristics. The biological properties were verified by 16S ribosomal RNA sequencing. Illumina metagenomic analysis was directly demonstrated from the water after DNA extraction via a membrane filtration pore of 0.45 µm. The range of pH, color and turbidity of water from the Phusang hot spring was 7.33-7.53, 0.05-0.18 Pt.Co and 9.55-10.91 NTU, respectively. The biological study of microorganisms found less than 300 CFU/mL. Coliform bacteria such as Staphylococcus aureus and other examples such as Aeromonas veronii, Acinetobacter sp. Neisseriaceae bacterium were abundant. Shotgun metagenomic sequencing defined the phylum as Proteobacteria (84%), Bacteroidetes (13%), Cyanobacteria (1%), and unclassified (2%). Moreover, the amount of sodium and strontium detected was 6.00-7.52 and 1.40-1.58 mg/L respectively. These studies show that a high abundance of Proteobacteria were present in samples from this hot spring. Phusang hot spring has been classified as having low mineral content water.